2022
DOI: 10.3102/01623737221086305
|View full text |Cite
|
Sign up to set email alerts
|

Informing School-Choosing Families About Their Options: A Field Experiment From New Orleans

Abstract: We conducted a randomized controlled trial to assess the effects of providing information to families as they choose schools. Likely applicants to prekindergarten, kindergarten, and ninth grade were assigned to one of three groups. A “growth” group received lists (via U.S. mail, email, and text message) of the highest performing schools they could request. A “distance” group received lists of schools in their home geographic zone. A “control” group did not see any schools highlighted. The growth treatment led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This is noteworthy given that value-added conveys more valid information about quality than test score levels (Harris, 2011;Kane & Staiger, 2002). However, value-added is also less readily available than test scores, and there is some evidence that shows when value-added is available it is utilized by families (Ainsworth et al, 2022;Valant & Weixler, 2020).…”
mentioning
confidence: 99%
“…This is noteworthy given that value-added conveys more valid information about quality than test score levels (Harris, 2011;Kane & Staiger, 2002). However, value-added is also less readily available than test scores, and there is some evidence that shows when value-added is available it is utilized by families (Ainsworth et al, 2022;Valant & Weixler, 2020).…”
mentioning
confidence: 99%
“…Findings showed that families who received this information, coupled with follow-up phone calls from a childcare resource and referral agency, were more likely to choose a provider with a higher rating than the control group that did not receive customized information or phone calls. In contrast, Valant and Weixler (2020) found that giving New Orleans families information about the quality of their pre-K options did not lead them to choose programs with higher program quality, even though a similar intervention for families of ninth-graders in the same school district did show benefits. More research is needed to better understand the potential of information efforts in other contexts.…”
Section: Within-sector Improvementsmentioning
confidence: 82%
“…Providing and streamlining information. K-12 research has shown that providing parents clear information about schooling options for their children can impact their choices and lead them to select higher-quality schools (Corcoran et al 2018;Hastings and Weinstein 2008;Valant and Weixler 2020). Providing information to families may be even more beneficial in ECE given the more decentralized context.…”
Section: Within-sector Improvementsmentioning
confidence: 99%
“…Although families can get rough estimates of this school information through word of mouth, social networks, and online reviews, the problem is that almost no parents directly observe what happens in schools, and almost everything they see is filtered through the minds of their adolescents and teenagers. As further evidence, experiments providing families with additional information generally lead to changes in their schooling choices (Hastings & Weinstein, 2008;Valant & Weixler, 2022). Although these effects are typically small, the fact that they have any effect at all is noteworthy, given the other constraints parents face in gaining access to schools (e.g., geographic proximity) that would keep them from using new information to alter their decisions.…”
Section: Families Have Imperfect Informationmentioning
confidence: 92%